Investigating Work Value, Job Satisfaction and Organizational Commitment Among National Electric Company Employees - Nancy Yusnita (University of Merdeka Malang, 2022)
The purpose of this study was to examine the factors that influence organizational commitment, namely work value and job satisfaction. The research was conducted at the State Electricity Company (PT PLN) in the West Java region, using quantitative methods with a regression approach (path analysis) and using quantitative data (from questionnaires). Research respondents consisted of 210 permanent employees. In general, this study aims to determine the efforts that can be made to increase employee commitment to the organization. The results show that there is a positive influence of work value on job satisfaction, there is a positive influence of work value on organizational commitment, there is a positive influence of job satisfaction on organizational commitment, there is a positive influence of work value on organizational commitment through job satisfaction. the most influential on work value, the job itself factor is the most influential on job satisfaction and normative commitment factor is the most influential on organizational commitment. This study proposes several recommendations to employees at the State Electricity Company Ltd (PT PLN). Improve indicators that have a high contribution to commitment to the organization. With the improvement of these indicators, it can be predicted that it will increase employee commitment to the organization